Effect of Gamma Ray Radiation 60Co Generation M1 on Growth and Production of Cayenne Pepper (Capsicum frutescens L) Prentul Kediri Variety - Agnes Septiya Nuraning Tias; Ida Retno Moeljani; Guniarti (Nusantara Science and Technology Proceedings, 2021)
Prentul cayenne pepper is a local chili in Kediri which is widely cultivated by local farmers, the continuity of chili needs to be maintained by increasing productivity. This can be overcome by improving local varieties through plant breeding activities. This study aims to determine the effect of radiation and obtain the optimal dose on the growth and production of cayenne pepper plants in the M1 generation. This research was carried out with the single plant method and using the T test, with a radiation dose of 100 Gy to 1000 Gy, and without a radiation dose or 0 Gy. Observation parameters included plant growth percentage, plant height, number of leaves, leaf width, flowering age and fruit weight. The results showed that the LD50 value of chili (Capsicum anuum L) was 572,917 Gy. The irradiation dose of 100 Gy gave the best effect on the growth and production of chili plants which had a plant height of 83.85 cm, a number of 35 leaves, a faster flowering age of 63 DAP and a fruit weight of 10.26. Gamma radiation affects plant growth. Different results were shown in the phenotypic appearance of leaf shape and fruit size. Meanwhile, at a dose of 300 Gy, it gave an effect that caused the plants to become stunted and have a longer harvest age, with the highest diversity value based on the standard deviation value of 23.93.